Selection and Validation of siRNAs Preventing Uptake and Replication of SARS-CoV-2 - Friedrich, Maik; Pfeifer, Gabriele; Binder, Stefanie; Aigner, Achim; Vollmer Barbosa, Philippe; Makert, Gustavo R.; Fertey, Jasmin; Ulbert, Sebastian; Bodem, Jochen; König, Eva-Maria; Geiger, Nina; Schambach, Axel; et al. (Frontiers in bioengineering and biotechnology, 2022)
In 2019, the novel highly infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak rapidly led to a global pandemic with more than 346 million confirmed cases worldwide, resulting in 5.5 million associated deaths (January 2022). Entry of all SARS-CoV-2 variants is mediated by the cellular angisin-converting enzyme 2 (ACE2). The virus abundantly replicates in the epithelia of the upper respiratory tract. Beyond vaccines for immunization, there is an imminent need for novel treatment options in COVID-19 patients. So far, only a few drugs have found their way into the clinics, often with modest success. Specific gene silencing based on small interfering RNA (siRNA) has emerged as a promising strategy for therapeutic intervention, preventing/limiting SARS-CoV-2 entry into host cells or interfering with viral replication. Here, we pursued both strategies. We designed and screened nine siRNAs (siA1-9) targeting the viral entry receptor ACE2. SiA1, (siRNA against exon1 of ACE2 mRNA) was most efficient, with up to 90% knockdown of the ACE2 mRNA and protein for at least six days. In vitro, siA1 application was found to protect Vero E6 and Huh-7 cells from infection with SARS-CoV-2 with an up to ∼92% reduction of the viral burden indicating that the treatment targets both the endosomal and the viral entry at the cytoplasmic membrane. Since the RNA-encoded genome makes SARS-CoV-2 vulnerable to RNA interference (RNAi), we designed and analysed eight siRNAs (siV1-8) directly targeting the Orf1a/b region of the SARS-CoV-2 RNA genome, encoding for non-structural proteins (nsp). As a significant hallmark of this study, we identified siV1 (siRNA against leader protein of SARS-CoV-2), which targets the nsp1-encoding sequence (a.k.a. ‘host shutoff factor’) as particularly efficient. SiV1 inhibited SARS-CoV-2 replication in Vero E6 or Huh-7 cells by more than 99% or 97%, respectively. It neither led to toxic effects nor induced type I or III interferon production. Of note, sequence analyses revealed the target sequence of siV1 to be highly conserved in SARS-CoV-2 variants. Thus, our results identify the direct targeting of the viral RNA genome (ORF1a/b) by siRNAs as highly efficient and introduce siV1 as a particularly promising drug candidate for therapeutic intervention.